POTENSI PENGGUNAAN METIL EUGENOL TERHADAP HAMA LALAT BUAH Bactrocera spp. (DIPTERA : TEPHRITIDAE) PADA TANAMAN LABU SIAM Sechium edule (Jacq) Sw. DI KOTA TOMOHON - Chika C. Maarebia; Dantje Tarore; Maxi Lengkong (COCOS, 2022)
ABSTRACT One of the subtropical plants that are often found in Indonesia is the chayote plant (Sechium edule (Jacq) Sw., whose fruit is used as food and is a vegetable consumed by the general public. The genus Bactrocera is reported to have 440 species and the family Tephritidae is the largest group of the order Diptera which is an important family because it is economically very detrimental because it acts as the main insect pest. The aim of the study was to determine the effectiveness of the use of methyl eugenol as an attractant against the type and population of the fruit fly Bactrocera spp. (Diptera:Tephritidae) on chayote plants S. edule (Jacq) Sw. in the city of Tomohon. The research was carried out using a survey method using traps at several chayote planting centers. In the experimental plot, three locations were chosen, each location was placed two traps on the east and west, the traps that were installed were traps made of modified mineral water plastic bottles, sprayed curacron insecticide into the trap bottles, cotton rolled with a diameter of approx. two cm were then tied and dropped with two ml of methyl eugenol using a syringe and then hung on the center of the trap bottle, the number of traps from the entire location was six bottles. The results of the research on the types of fruit flies caught in chayote cultivation using methyl eugonal as an attractant were B. dorsalis, B. carambolae, B. umbrosa, B. albistrigata, and B. cucurbitae. The use of methyl eugenol as an attractant was able to catch several types of fruit flies in the Kakaskasen sub-district as many as 478 tails, Talete 1 as many as 290 tails, and Talete 2 as many as 269 tails with a total catch of 1033 tails. Keyword : potential, methyl eugenol, Bactrocera spp, Sechium edule